Performance Evaluation of Wastewater Treatment Plants in the Medical Device Manufacturing Industry - Arif, Ady Syah Putra; Farahdiba, Aulia Ulfah (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This study evaluates the performance and effectiveness of a Wastewater Treatment Plant (WWTP) at a medical device manufacturing facility with a capacity of 6 m3/day. Based on laboratory analysis, the parameters for BOD, COD, TSS, pH, ammonia, and total coliform in the effluent comply with the quality standards stipulated in the Regulation of the Minister of Environment No. 5 of 2014. However, oil and grease parameters showed 0% removal efficiency and failed to meet the standards due to the absence of a specific treatment unit, such as a grease trap. Technical evaluations revealed significant discrepancies in detention times across several primary units. The detention time in the equalisation tank reached 48 hours, far exceeding the design criterion of <2 hours, triggering anaerobic conditions and odour issues. In the aerobic biofilter units, pollutant degradation was suboptimal due to the lack of contact media for microorganism biofilm formation. Furthermore, the sedimentation unit experienced excessive detention time of 12 hours and operational disruptions due to turbulence from existing diffusers, hindering particle settling. This study recommends adding a grease trap, installing biofilter media (such as bioballs or honeycombs), and removing diffusers from the sedimentation tank to optimise treatment efficiency. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 12: Responsible Consumption and Production